Exploring preservice teachers' affective and behavioural responses towards inclusive education: A qualitative inquiry - Mohamad Izan, Syafiqa Qadrina; Mohammad Zaidi, Nurul Asyhmeera; Rusli, Amalia Aina; Teng, Kie Yin; Lee, Hou Yew (Jurnal Pendidikan Bitara UPSI, 2025)
This qualitative study explores preservice teachers’ perceptions of inclusive education (IE), focusing on their preparedness, challenges, and emotional and behavioural responses during practicum, as well as strategies that support effective inclusion. Data was collected through semi-structured interviews with six preservice teachers and analysed thematically across two key domains: affective and behavioural. The affective domain highlights preservice teachers’ emotions, attitudes, and values toward IE, while the behavioural domain addresses instructional practices such as differentiated instruction, peer support, and use of assistive technologies. Findings reveal themes including emotional preparedness, communication challenges, instructional adaptation, and classroom management. Although participants demonstrate a strong commitment to inclusion, many feel unprepared to manage classroom dynamics and engage students with special educational needs (SEN), particularly those with autism spectrum disorder (ASD) or hearing impairments. The study underscores the need for experiential learning in teacher education programmes and improved support systems to enhance effective and behavioural competencies in inclusive settings. Despite limitations such as small sample size and reliance on self-reports, this study contributes to ongoing discussions on inclusive teacher training and offers practical recommendations for future research and practice. These limitations were acknowledged to maintain transparency in the findings and to suggest future research directions using triangulation and a broader sample base.